THE EVOLVING IMAGE OF WOMEN IN INDIAN ADVERTISEMENTS: A REVIEW - Jeyarani, J.; Vasanthan, R. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Ads, also known as adverts or advertisements, are typically seen as a form of public communication aimed at promoting a product, service, brand, or event. The purpose of such ads is to convey the benefits of the product to the audience through visually appealing print or visual media. Advertisements play a crucial role in driving sales by tapping into consumer desires and shaping cultural trends. Companies spend significant amounts on marketing their products through advertising. Over time, the representation of women in advertisements has been changing, moving away from stereotypical portrayals. This paper examines the evolution of the image of women in Indian advertisements.